The Influence of Committee Chairman's Managerial Ability on Learning Process at Public Junior High School - Musriyadi (Nalar Global Foundation, 2021)
Managerial ability is a leader's ability to use resources and tools so that their use is efficient and effective. Based on this background, this study aims to find out how the managerial ability of the committee chairman at the Batam City Junior High School, the smooth learning process at the Batam City State Junior High School, and whether there is an influence of the committee chairman's managerial ability on the smooth learning process at the Batam City Junior High School. The population in this study were 35 committee heads at SMP Negeri Batam City, the data were collected through questionnaires, documentation. Data were analyzed by simple linear regression. The results of this study indicate that: (1) the managerial ability of the committee chairman is sufficient by obtaining a questionnaire score of 68.57% (2) The smoothness of the learning process at SMP Negeri Batam City is classified as good by obtaining a questionnaire score of 65.71%, (3) There is a positive and significant influence the managerial ability of the committee chairman to the smooth learning process at the Batam City Junior High School. It can be seen from the rcount value of 0.433 which is greater than the value of rtable = 0.344. Meanwhile, the managerial ability of the committee chairperson has an influence on the smoothness of the learning process at the Batam City Junior High School by 18.7%.